(untitled) (Fiep Bulletin - online, 2016)
There is a relationship between the localized exercise and fat loss in the adjacent muscle recruited adipose tissue. Metabolic functions of the subcutaneous adipose tissue are closely related to your blood stream, and exercise a modulator of blood flow in adipose tissue. In this sense, the objective is to verify the relationship between the loss of fat located adjacent to muscle recruited and not recruited athletes in women’s handball. The study was conducted with athletes from the women’s team handball from Fortaleza / IFCE. An anthropometric assessment by skinfold measurement was performed following Recruited Recruited and not the acceleration phase of throwing handball, height and body mass. From the data collected it was found that the average height of the participating athletes was 1,62m weighing 62.7 on average, and BMI, 23.77. Regarding the comparison of body fat of the dominant and non-dominant segments, we found that the values ??were generally similar. The pectoral skinfold, suprailiac and midaxillary dominant segments of lower values ??were found in measures of adipose tissue from 8.8 to 9.0, 13.2 to 13.6; 17.6 -17.8 respectively. In contrast, biceps skinfold, triceps and subscapular the dominant members had higher values??, being 7.95 to 7.78; 15.73 to 15.44; 17.96 to 17.53 respectively. It was concluded that there was no loss of fat located adjacent to the trained muscle, making it necessary to use more reliable instruments such as DEXA and MRI in future studies.